Pengaruh Terpaan Konten Video #Racunshopee Di Tiktok Terhadap Perilaku Konsumtif: Studi Kausalitas Pengaruh Terpaan Konten Video #racunshopee di TikTok terhadap Perilaku Konsumtif pada Remaja SMAN 1 Subang - Nadhiv Irvina Wibawa; Nur'aeni; Akhmad Basuni (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This research is entitled The Effect of Exposure to #racunshopee's Video Content on TikTok on Consumptive Behavior (A Causality Study of Exposure to #racunshopee's Video Content on TikTok on Consumptive Behavior in Adolescents at SMAN 1 Subang). Then this research uses the S-O-R Theory. The purpose of this study is to find out how much exposure to #racunshopee's video content is on TikTok, how much consumptive behavior is on #racunshopee's video content. And how big is the impact of exposure to #racunshopee's video content on TikTok on consumptive behavior. The approach used in this research is quantitative with the type of associative. The respondents of this study were teenagers who were students of SMAN 1 Subang who watched and watched the video content of #racunshopee on TikTok. The sampling technique used is a saturated sample (census), while the number of respondents in this study is 97 people. Based on the research results of hypothesis testing through t test, it is known that t count = 8.203 with a significant level of 0.5 and t table = 1.66105. H0 is rejected and Ha is accepted because t arithmetic is greater than t table then. Therefore, it can be concluded that exposure to #racunshopee's video content on TikTok (X) has an effect on consumptive behavior (Y) and the magnitude of the effect is 41.5% and 58.5% is influenced by factors other than the variables studied in this study.   Keywords: #racunshopee video content, exposure, consumptive behavior